Synthesis and applications of electrospun nanofibers - Asmatulu, Ramazan; Khan, Waseem S. (Micro & nano technologies., 2019)
Synthesis and Applications of Electrospun Nanofibers examines processing techniques for nanofibers and their applications in a variety of industry sectors, including energy, agriculture and biomedicine. The book gives readers a thorough understanding of both electrospinning and interfacial polymerization techniques for their production. In addition, the book explore the use of nanofibers in a variety of industry sectors, with particular attention given to nanofibers in medicine, such as in drug and gene delivery, artificial blood vessels, artificial organs and medical facemasks, and in energy and environmental applications. Specific topics of note include fuel cells, lithium ion batteries, solar cells, supercapacitors, energy storage materials, sensors, filtration materials, protective clothing, catalysis and electromagnetic shielding. This book will serve as an important reference resource for materials scientists, engineers and biomedical scientists who want to learn more on the uses of nanofibers.